2012
DOI: 10.5267/j.msl.2011.11.015
|View full text |Cite
|
Sign up to set email alerts
|

A study on convention on the elimination of all forms of discrimination against women

Abstract: For many years, there was much discrimination against women in the world in terms of social benefits, job opportunities, etc. In many cases, women received less for similar job than men did and in some cases, many important top management jobs were not even open for women. During the past few decades, there have been tremendous efforts on removing any discrimination laws and regulations against women. In this study, we present a study on convention on the elimination of all forms of discrimination against wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…They also concluded that Iranian women were quite forward and there would be definite reasons for drop out. Mansouri (2012), in other study, investigated on convention on the elimination of all forms of discrimination against women in Iran. Tajbakhsh et al (2013) selected a sample from all female students who were enrolled in educational studies in Shiraz university, Iran and using Pearson correlation test, they measured the relationship between seven mentioned items with respect for women.…”
Section: Introductionmentioning
confidence: 99%
“…They also concluded that Iranian women were quite forward and there would be definite reasons for drop out. Mansouri (2012), in other study, investigated on convention on the elimination of all forms of discrimination against women in Iran. Tajbakhsh et al (2013) selected a sample from all female students who were enrolled in educational studies in Shiraz university, Iran and using Pearson correlation test, they measured the relationship between seven mentioned items with respect for women.…”
Section: Introductionmentioning
confidence: 99%